Nerve-sparing radical hysterectomy: steps to standardize surgical technique. Issue 7 (September 2019) - Muallem, Mustafa Zelal; Diab, Yasser; Sehouli, Jalid; Fujii, Shingo
Abstract : Aim: The primary objective of this review was to study and analyze techniques of nerve-sparing radical hysterectomy so as to be able to characterize and elucidate intricate steps for the dissection of each component of the pelvic autonomic nerve plexuses during nerve-sparing radical hysterectomy. Methods: This review was based on a five-step study design that included searching for relevant publications, selecting publications by applying inclusion and exclusion criteria, quality assessment of the identified studies, data extraction, and data synthesis. Results: There are numerous differences in the published literature concerning nerve-sparing radical hysterectomy including variations in techniques and surgical approaches. Techniques that claim to be nerve-sparing by staying above the dissection level of the hypogastric nerves do not highlight the pelvic splanchnic nerve, do not take into account the intra-operative patient position, nor the fact that the bladder branches leave the inferior hypogastric plexus in a ventrocranial direction, and the fact that inferior hypogastric plexus will be drawn cranially with the vaginal walls (if this is not recognized and isolated earlier) above the level of hypogastric nerves by drawing the uterus cranially during the operation. Conclusions: The optimal nerve-sparing radical hysterectomy technique has to be radical (type C1) and must describe surgical steps to highlight all three components of the pelvic autonomic nervous system (hypogastric nerves, pelvic splanchnic nerves, and the bladder branches of the inferior hypogastric plexus). Recognizing the pelvic splanchnic nerves in the caudal parametrium and the isolation of the bladder branches of the inferior hypogastic plexus requires meticulous preparation of the caudal part of the ventral parametrium.